2009
DOI: 10.1007/s12010-009-8590-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Phosphate-Solubilizing Fungi from Phosphate Mines and Their Effect on Wheat Seedling Growth

Abstract: Three phosphate-solubilizing fungi, identified as Penicillium expansum, Mucor ramosissimus, and Candida krissii, were isolated from phosphate mines (Hubei, People's Republic of China) and characterized. All the isolates demonstrated diverse levels of phosphate-solubilizing capability in National Botanical Research Institute's phosphate growth medium containing rock phosphate as sole phosphate source. Acidification of culture medium seemed to be the main mechanism for rock phosphate solubilization. Indeed, citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…This may be due to better utilization of soluble phosphorus from the pool of available phosphorus in the soil due to solubilization of native and added phosphorus by the actions of the PSF isolates. This result is in agreement with previous reports of Xiao et al (2009) Increased nitrogen content in the leaves of haricot bean plants was recorded by the inoculation of PSF isolates compared to the control. The increase in nitrogen content of haricot bean might be due to increased nodulation as well as the positive interaction between P-solubilizing fungal isolates and root nodulating bacteria.…”
Section: Discusssupporting
confidence: 94%
See 2 more Smart Citations
“…This may be due to better utilization of soluble phosphorus from the pool of available phosphorus in the soil due to solubilization of native and added phosphorus by the actions of the PSF isolates. This result is in agreement with previous reports of Xiao et al (2009) Increased nitrogen content in the leaves of haricot bean plants was recorded by the inoculation of PSF isolates compared to the control. The increase in nitrogen content of haricot bean might be due to increased nodulation as well as the positive interaction between P-solubilizing fungal isolates and root nodulating bacteria.…”
Section: Discusssupporting
confidence: 94%
“…The increase in plant shoot height due to PSF inoculation along with RP application could be the result of increased transformation of P into available forms as indicated by the increased P in plants by the PSF isolates PSFAand PSFP. Similar results of increase in shoot height due to PSF inoculation has been reported on groundnut plant (Malviya et al, 2011), wheat (Xiao et al, 2009), chickpea (Yadav et al, 2011) and soy bean (Iman, 2008).…”
Section: Discusssupporting
confidence: 81%
See 1 more Smart Citation
“…However subsequently a significant drop in soluble phosphorus level was observed on later days when incubation period progressed. This may be due to the availability of soluble phosphorus in the culture medium, which has an inhibitory effect on further phosphate solubilization (Xiao et al, 2009). Some researchers suggested that it is due to the depletion of nutrients in the culture medium especially carbon source for the production of organic acids and microbial activity (Kang et al, 2002;Kim et al, 2005;Chaiharn and Lumyong, 2009).…”
Section: Assay Of Inorganic Phosphate Solubilizing Abilitiesmentioning
confidence: 99%
“…Most P are immobile and the available content of P is below the limit of plant growth in soils. Microorganisms play an important role in rendering insoluble P into soluble forms that are utilized by plants and prompt plant growth (Mehta et al, 2013;Xiao et al, 2009). Many studies have proven that acidification is the most process of P solubilization (Xiao et al, 2015;Sindhu et al, 2014;Rodríguez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%